ZAKAT DAN WAKAF DALAM MENDUKUNG PENGEMBANGAN USAHA MIKRO KECIL MENENGAH - Nur Habib, Asifi Antoni; Nur Ilma, Aidah; Pramiswari, Diva Ayu; Lestari, Dwi; Latifah, Eny (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
The aim of this research is to determine zakat and waqf in supporting the development of micro, small and medium enterprises. The research method used is a library method by combining data sources originating from books, journals and reports of previous research results. The results of this research are that zakat and waqf have a very important contribution in helping and supporting the development of micro, small and medium enterprises. With the existence of some zakat and waqf assets, the community's economy is greatly helped and most UMKM have felt the benefits of zakat and waqf in helping the prosperity of their small businesses.